The effect of using interactive e-books on students’ mastery of learning competencies in science 9 - Sharon M. Ananayo (CV Rezki Media, 2022)
Even in the midst of the COVID-19 pandemic, learning has to continue. With this, different learning modalities were employed, and different teaching strategies were explored. This research investigated the effect of using interactive e-books on students’ mastery of learning competencies in science 9. Explanatory Sequential Mixed Methods Research Design was used wherein the quantitative data were gathered and analyzed first then followed by the collection and analysis of qualitative data. The participants were 17 students from the control group and another 17 from the experimental group, who were selected through purposive sampling. The control group was employed with two-way radio-guided modular distance learning modality while the experimental group utilized the developed interactive e-books. Findings revealed that the utilization of e-books has significantly improved the mastery level of the students. In addition, e-book utilization does not present any learning differences when compared to the two-way radio-guided modular distance learning modality indicating that this strategy is as effective as the two-way radio-guided instruction. The improvement in the mastery level of the students could be attributed to the positive feedback of the users on the interactive e-books, which include user satisfaction, clarity of multimedia, playability of e-books, and benefits of using e-books. However, some students have experienced minor difficulty with the installation of e-books.